The association between white blood cell subtypes and prevalence and incidence of nonalcoholic fatty liver disease. (March 2019) - Zhang, Hongmei; Niu, Yixin; Gu, Hongxia; Lu, Shuai; Su, Weikang; Lin, Ning; Li, Xiaoyong; Yang, Zhen; Qin, Li; Su, Qing
The association between white blood cell (WBC) and nonalcoholic fatty liver disease (NAFLD) has been studied before, but whether different WBC subtypes were related to NAFLD was not detailed. The aim of our study was to investigate the relationship between WBC subtypes and NAFLD cross-sectionally and prospectively. The detailed research design has been described previously. At baseline, there were 9930 participants who had complete information, in the end a total of 8079 participants (2588 men and 5491 women) were eventually included in this study. Hepatic ultrasound examination was performed on each participant at baseline and at the end of follow-up. Alcohol abuse and hepatitis were excluded. WBC subtypes and other serum indices were measured at baseline. We found that the total WBC, neutrophil, and lymphocyte counts were independently associated with the prevalence and incidence of NAFLD. After multiple adjustments for age, gender, body mass index (BMI), insulin, HOMA-IR, TG, TC, LDL, and HDL, increased odds ratios (ORs) for new onset NAFLD were observed from the 1st to the 4th quartiles of WBC, neutrophil, and lymphocyte (all P  < 0.001 for trend). In conclusion, total WBC counts, neutrophils, and lymphocytes were all independent risk factors for NAFLD in the rural Chinese population. The association was independent of insulin resistance.